Novel Nrf2 activators from microbial transformation products inhibit blood–retinal barrier permeability in rabbits. (12th January 2015) - Nakagami, Yasuhiro; Masuda, Kayoko; Hatano, Emiko; Inoue, Tatsuya; Matsuyama, Takuya; Iizuka, Mayumi; Ono, Yasunori; Ohnuki, Takashi; Murakami, Yoko; Iwasaki, Masaru; Yoshida, Kazuhiro; Kasuya, Yuji; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Nuclear factor erythroid 2‐related factor 2 (Nrf2) is a redox‐sensitive transcription factor that binds to antioxidant response elements located in the promoter region of genes encoding many antioxidant enzymes and phase II detoxifying enzymes. Activation of the Nrf2 pathway seems protective for many organs, and although a well‐known Nrf2 activator, bardoxolone methyl, was evaluated clinically for treating chronic kidney disease, it was found to induce adverse events. Many bardoxolone methyl derivatives, mostly derived by chemical modifications, have already been studied. However, we adopted a biotransformation technique to obtain a novel Nrf2 activator. Experimental Approach The potent novel Nrf2 activator, RS9, was obtained from microbial transformation products. Its Nrf2 activity was evaluated by determining NADPH:quinone oxidoreductase‐1 induction activity in Hepa1c1c7 cells. We also investigated the effects of RS9 on oxygen‐induced retinopathy in rats and glycated albumin‐induced blood–retinal barrier permeability in rabbits because many ocular diseases are associated with oxidative stress and inflammation. Key Results Bardoxolone methyl doubled the specific activity of Nrf2 in Hepa1c1c7 cells at a much higher concentration than RS9. Moreover, the induction of Nrf2‐targeted genes was observed at a one‐tenth lower concentration of RS9. Interestingly, the cytotoxicity of RS9 was substantially reduced compared with bardoxolone methyl. Oral and intravitreal administration of RS9 ameliorated the pathological scores and leakage in the models of retinopathy in rats and ocular inflammation in rabbits respectively. Conclusion and Implications Nrf2 activators are applicable for treating ocular diseases and novel Nrf2 activators have potential as a unique method for prevention and treatment of retinovascular disease.